Socio-demographic factors influencing the use of free maternal health services among pregnant women - Ronoh, Godfrey Kipsang; Muchiri, Joseph; Suleiman, Mbaruk (International Journal Of Community Medicine And Public Health, 2025)
Background: Maternal health remains a major public health challenge, particularly in low- and middle-income countries. Despite Kenya’s efforts to provide free maternal healthcare, maternal mortality rates remain high in Turkana Central Sub-County due to socio-cultural, economic, and infrastructural barriers. Methods: A cross-sectional study was conducted in Turkana Central Sub-County to assess factors influencing the uptake of free maternal health services. Data were collected using structured questionnaires and focus group discussions. Quantitative data were analyzed using SPSS version 29, employing chi-square tests and logistic regression to examine associations between socio-demographic factors and service utilization. A significance level of p<0.05 was applied. Results: The study included 210 participants, most aged 20-24 (16.2%) and married (49.0%). The majority were Christians (82.5%) and self-employed (63.3%), with 79.5% having no or only primary education. Age (p=0.012), parity (p=0.011), and household income (p=0.013) were significantly associated with service utilization, while marital status, religion, income source, and education level were not. Women aged 25-29 were less likely to utilize free maternal health services (OR=0.141, p=0.007), whereas lower-income women (Ksh. 0-2,500) were more likely (OR=2.584, p = 0.036). Higher income levels correlated with decreased uptake. Conclusions: Age, parity, and household income significantly influenced the utilization of free maternal health services. Financial constraints remain a key determinant, with lower-income women more reliant on free services. Efforts to improve maternal health should prioritize increasing awareness and accessibility.